Gambaran Metode Menyikat Gigi dan Skor Plak pada Siswa Kelas V dan VI SD Negeri 2 Sidayu - Putri Nur Pritayanti; Quroti Ayun; Etty Yuniarly (Poltekkes Kemenkes Yogyakarta, 2017)
Tooth brushing methods is the common way to clean soft deposit in the teeth and gum surface as a preventive effort to check the optimal health condition of mouth. Plaque is uncolored thin tissue (transparent), unseen only by the normal eye, attached in the teeth and make colony form. The purpose of this researchwasto knowthe description of tooth brushing methods and plaque score of class V and VI studentsat Sidayu 2 Elementary School. This research used descriptive quantitative research. The sample of this research was taken from students of class V and VI with total number of 40 students. Aspects inspected in this study were tooth brushing methods and plaque score. Data of the result in this research were managed and analyzed by cross tabulation table. The result of this research based on the gender was 25 male students and 15 female students. In the other side, based on age, there were 16 students at the age of 12 years old at the most. Tooth brushing method that the most respondent used was roll method which done by 14 respondents (35%), while plaque score criteria that the most respondents had was in average criteria. In the conclusion, based on crosstab between tooth brushing methods and plaque score, the description of the tooth brushing methods and plaque score in students of class V and VI was horizontal method with bad criteria of plaque score as many as 9 respondents (22,5%) and combination method with averagecriteria of plaque score as many as 9 respondents (22,5%).